2021
DOI: 10.1007/s11102-021-01153-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgically treated acromegaly patients have a similar quality of life whether controlled by surgery or requiring additional medical therapy (QuaLAT Study)

Abstract: Purpose There is no consensus on quality of life (QOL) in patients with acromegaly requiring medical treatment after surgery compared with those achieving remission by surgery alone. Methods QuaLAT is a cross-sectional study comparing QOL in surgery-only treated acromegaly patients versus those requiring medical treatment post-surgery. Patients attending clinics were identified and divided into—Group 1: patients who had surgery only and were in biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Little et al was the only paper to include a complete racial and ethnic distribution of all 113 participants. 17 One additional paper (Arshad et al 18 ) noted that information on ethnicity was collected, but that data were not reported in the printed publication. ►Fig.…”
Section: Race and Ethnicity Datamentioning
confidence: 99%
“…Little et al was the only paper to include a complete racial and ethnic distribution of all 113 participants. 17 One additional paper (Arshad et al 18 ) noted that information on ethnicity was collected, but that data were not reported in the printed publication. ►Fig.…”
Section: Race and Ethnicity Datamentioning
confidence: 99%
“…Other available options include medical and radiotherapy. However, despite the multiple options for treatment, approximately 40% of patients remain uncontrolled [ 77 ]; and more importantly, regardless of biochemical control, health-related quality of life remains unimproved [ 78 ]. There is often a delay in treatment owing to delayed diagnosis as well, as symptom development in acromegaly can take years [ 79 ].…”
Section: Current Problems and Possible Future In Acromegaly Managementmentioning
confidence: 99%
“…As such, studies are looking into innovations in treatment to a precision medicine which can direct treatment in a more individualized approach. Moreover, new drugs for acromegaly are being developed, with potential to further improve disease control [ 78 ]. Lastly, attempts at earlier diagnosis and treatment can decrease progression of disease and its associated comorbidities.…”
Section: Current Problems and Possible Future In Acromegaly Managementmentioning
confidence: 99%